2022
DOI: 10.3389/fsufs.2022.1025538
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the growth performance and carcass composition of Nile tilapia (Oreochromis niloticus) fed dietary copra meal

Abstract: IntroductionNile tilapia (Oreochromis niloticus) is one of the most cultured species in the aquaculture industry. However, its market price is affected by the increasing cost of fishmeal. Plant-based proteins are being used to mitigate the problem.MethodologyThis paper comprehensively quantified the growth performance and carcass composition of Nile tilapia fed copra meal via systematic review and meta-analysis. The literature review and paper selection were done based on the preferred reporting items for syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since the conventional fish feed is found to be contaminated with different anthropogenic contaminants including microplastics, the fish farmers should think of sustainable protein soured alternatives like insect protein, or plant protein. According to a recent study conducted by Magbanua and Ragaza, 2022 [ 84 ], regional sources of plant-based proteins, including soybean, corn, palm kernel, and pea meal, have been identified as highly promising substitutes for fishmeal. Plant-based proteins are readily accessible in the commercial sphere and exhibit a substantial quantity and commendable quality of protein content.…”
Section: Resultsmentioning
confidence: 99%
“…Since the conventional fish feed is found to be contaminated with different anthropogenic contaminants including microplastics, the fish farmers should think of sustainable protein soured alternatives like insect protein, or plant protein. According to a recent study conducted by Magbanua and Ragaza, 2022 [ 84 ], regional sources of plant-based proteins, including soybean, corn, palm kernel, and pea meal, have been identified as highly promising substitutes for fishmeal. Plant-based proteins are readily accessible in the commercial sphere and exhibit a substantial quantity and commendable quality of protein content.…”
Section: Resultsmentioning
confidence: 99%
“…The potential incorporation of copra meal in aquaculture feed diets was also tested in various species, particularly in Nile and saline tilapia, milkfish, and black tiger shrimp, in the studies conducted by Obirikorang et al [ 15 ], Harlina et al [ 14 ], Magbanua and Ragaza [ 56 ], Apines-Amar et al [ 13 ], and Corre et al [ 17 ], respectively. Similar to the trend observed for other experimental diets for animals using copra meal, the inclusion of CM resulted in lower feed bulk density.…”
Section: Copra Meal As An Animal Feed Ingredientmentioning
confidence: 99%
“…In terms of aquaculture feed applications, it would be critical to examine the physical characteristics, particularly the hardness, water stability, water absorption index, and water solubility index, as these are important indicators of the nutrient retention capacity and sinking velocity of feed pellets. The hardness of feeds is also highly correlated to the animal’s preference, especially in aquatic species, as studies have found that fish prefer softer pellets than harder ones and the high concentration of CM in experimental feed diets result in lower feed intake [ 56 ]. Note that the inclusion of plant ingredients in feed has significant effects on the physical properties of the product, since the NSPs have the potential to reduce the expansion and increase the hardness.…”
Section: Propertiesmentioning
confidence: 99%
“…In aquaculture, the tilapia industry is one of the most stable and steady-growing. Nile tilapia (Oreochromis niloticus) is the best-ranked and most substantial tilapia species being cultivated and traded [1]. With rapid progress and intensification in the aquaculture industry, various emerging diseases have arisen [2].…”
Section: Introductionmentioning
confidence: 99%